2013
DOI: 10.1038/ijos.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and interleukin-4 detected in serum and saliva from patients with oral lichen planus

Abstract: Our previous salivary study had demonstrated an apparent T helper 2 (Th2)-predominance in saliva of oral lichen planus (OLP) patients and suggested a potential of salivary interleukin-4 (IL-4) as a biomarker for monitoring disease severity. To further determine the consistency of Th1/Th2 bias of OLP, this study investigated the expression profile of interferon-γ (IFN-γ) and IL-4 in serum and the relationship of the serum levels of these cytokines with their saliva partners. Sixty ethnic Chinese patients with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
3
28
1
1
Order By: Relevance
“…The imbalance of Th1/Th2 has been established to be closely linked to the pathogenesis of OLP. 19,20 Our previous study, in accordance with other observations, identified a predominant immune imbalance of Th2 cells in the peripheral blood and saliva of patients with OLP. 21 As the CCL17-CCR4 axis has been confirmed to be strongly chemotactic for Th2 cells, the results of the present study show that the CCL17-CCR4 axis may be responsible for the predominant immune imbalance of Th2 cells in the peripheral blood of OLP patients.…”
Section: Discussionsupporting
confidence: 89%
“…The imbalance of Th1/Th2 has been established to be closely linked to the pathogenesis of OLP. 19,20 Our previous study, in accordance with other observations, identified a predominant immune imbalance of Th2 cells in the peripheral blood and saliva of patients with OLP. 21 As the CCL17-CCR4 axis has been confirmed to be strongly chemotactic for Th2 cells, the results of the present study show that the CCL17-CCR4 axis may be responsible for the predominant immune imbalance of Th2 cells in the peripheral blood of OLP patients.…”
Section: Discussionsupporting
confidence: 89%
“…This observation also implicates there are Th1‐relevant immunologic actions primarily, contributing to the deteriorative conditions in the disease. On the contrary, Liu et al () suggest that Th2 is predominant in OLP testified by evaluating salivary IL‐4 level from subjects. This discrepancy is unknown but partially may be caused by difference in the detected samples used.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that the cytokine profile in saliva, lesions, and serum of patients with OLP differs from that seen in healthy individuals (Dan et al, ; de Brito Monteiro et al, ; Kaur & Jacobs, ; Kondo & Urisu, ; Liu et al, ; Lu et al, ; Malekzadeh et al, ; Pekiner et al, ; Piccinni et al, ; Simark‐Mattsson et al, ; Wang et al, ; Zhou et al, ). In this study, we found that the serum levels of IL‐6 were higher in the patients than in the healthy control subjects and in accordance with previous findings that also found an association between levels of IL‐6 and the stages of OLP (Abdel‐Haq et al, ; Kaur & Jacobs, ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the expression of cytokines may reflect the extent of immune dysregulation and various roles of cytokines in the pathogenesis of inflammatory diseases such as OLP (Lu, Zhang, Sun, Du, & Zhou, ; Moudgil & Choubey, ). A number of studies have shown that the expression pattern of various inflammation‐related cytokines, including tumor necrosis factor (TNF)‐α, interferon (IFN)‐γ, and interleukin (IL‐)‐1, 2, 4, 5, 6, 8, 10, 12, 17, 22, in lesions, saliva, serum, and peripheral blood mononuclear cells (PBMCs) from patients with OLP differs from that seen in healthy control subjects (Dan et al, ; de Brito Monteiro et al, ; Kaur & Jacobs, ; Kondo & Urisu, ; Liu et al, ; Malekzadeh, Robati, Yousefimanesh, Ghafourian Boroujerdnia, & Nadripour, ; Pekiner, Demirel, Borahan, & Ozbayrak, ; Piccinni et al, ; Simark‐Mattsson et al, ; Wang, Zhou, Fu, Wang, & Zhou, ; Zhou et al, ). TNF‐α is one the most studied cytokines in OLP and is believed to play an important role in the immune regulation of OLP (Pezelj‐Ribaric et al, ).…”
Section: Introductionmentioning
confidence: 99%